2021
DOI: 10.3390/nano11081914
|View full text |Cite
|
Sign up to set email alerts
|

Seedless Cu Electroplating on Co-W Thin Films in Low pH Electrolyte: Early Stages of Formation

Abstract: The use of Ta/TaN barrier bilayer systems in electronic applications has been ubiquitous over the last decade. Alternative materials such as Co-W or Ru-W alloys have gathered interest as possible replacements due to their conjugation of favourable electrical properties and barrier layer efficiency at reduced thicknesses while enabling seedless Cu electroplating. The microstructure, morphology, and electrical properties of Cu films directly electrodeposited onto Co-W or Ru-W are important to assess, concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The 25 nm thick Co-W films were deposited by co-sputtering Co and W targets (99.95%, Testbourne Ltd., Basingstoke, UK) for 600 s in a DC magnetron sputtering system (Kenosistec, Binasco, Italy), at 40 W power for each of the targets used, using a constant Ar flux of 20 sccm. These conditions aimed to produce a film with a 1:1 atomic ratio, as used in [ 13 ]. The Ta film representing the reference adhesion layer material was deposited at 100 W for 380 s to produce a film of equal thickness, with a base pressure of 6.4 × 10 −5 Pa and working pressure of 6.9 × 10 −3 Pa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 25 nm thick Co-W films were deposited by co-sputtering Co and W targets (99.95%, Testbourne Ltd., Basingstoke, UK) for 600 s in a DC magnetron sputtering system (Kenosistec, Binasco, Italy), at 40 W power for each of the targets used, using a constant Ar flux of 20 sccm. These conditions aimed to produce a film with a 1:1 atomic ratio, as used in [ 13 ]. The Ta film representing the reference adhesion layer material was deposited at 100 W for 380 s to produce a film of equal thickness, with a base pressure of 6.4 × 10 −5 Pa and working pressure of 6.9 × 10 −3 Pa.…”
Section: Methodsmentioning
confidence: 99%
“…The use of Co-W as a candidate system for replacing the Ta/TaN has been suggested for seedless Cu metallization, potentially suppressing the need for a copper seed layer deposited by PVD (physical vapor deposition), thus eliminating one of the manufacturing steps necessary for the production of each copper interconnect layer [ 7 , 13 ]. While the work of Su et al [ 7 ] showed the use of Co-W as a directly plateable material for diffusion barrier layers, the effect of the annealing treatment on the copper layer deposited over the Co-W barrier was not addressed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodepositions were performed at room temperature and without electrolyte stirring using a Gamry potentiostat/galvanostat Interface 1000E (Gamry Instruments, Warminster, PA, USA). Additional details on the materials and electrolyte pH measurement can be found in [12]. The substrates were covered with a polymeric mask, limiting the exposed area to a circle of 0.50 cm 2 .…”
Section: Cu Electroplatingmentioning
confidence: 99%
“…Ru is chemically inert and stable, contrasting with its counterparts, such as Co, which is prone to dissolution during conventional acidic electroplating, requiring electrolyte modification to be used in seedless diffusion barrier systems [11,12]. However, similar to other candidates, Ru alone is not effective as a diffusion barrier [13], thus, driving the research on coupling Ru with other species to improve the barrier properties against Cu diffusion, including Ru-Co [14], Ru-Cr [15], Ru-Mn [16][17][18], Ru-N [19], Ru-P [20,21], Ru-Ta(-N) [16,22,23], and Ru-W(-N) [16,24,25] compositions.…”
Section: Introductionmentioning
confidence: 99%